Analysis of Early Reoperation and Mortality Following Intertrochanteric Fracture Fixation in Elderly Patients: A Focus on Frailty, Bone Quality, and Technical Factors - Karasu, Recep; Şahin, Namık; Dinç, Mustafa; Bayrak, Hünkar Çağdaş (The European Research Journal, 2026)
Objectives: Intertrochanteric femur fractures in older adults carry high risks of early complications and mortality. This study aimed to identify independent predictors of early fixation failure and postoperative mortality by integrating patient-, fracture-, and technique-related factors. Methods: This single-center retrospective cohort included 150 patients aged ≥65 years who underwent surgical fixation with a Dynamic Hip Screw (DHS) or Proximal Femoral Nail Antirotation (PFN-A) for the AO Foundation/Orthopaedic Trauma Association (AO/OTA) 31-A intertrochanteric fractures. Evaluated variables included comorbidity burden assessed using the Charlson Comorbidity Index, bone quality assessed using the Singh Index, pre-fracture mobility assessed using the Functional Ambulation Scale, fracture pattern, and reduction–fixation quality. Results: Early reoperation occurred in 12.6% of patients, and 6-month mortality was 24%. Independent predictors of early reoperation included fracture instability (AO/OTA 31-A3; adjusted odds ratio [aOR]=1.41) and higher Charlson Comorbidity Index score (aOR=2.47). In contrast, better bone quality (higher Singh Index; aOR=0.16), superior reduction–fixation quality (aOR=0.12), and higher pre-fracture mobility (aOR=0.75) were protective against reoperation. Early mortality was independently associated with a higher Charlson Comorbidity Index score (aOR=1.74), poorer bone quality (aOR=0.42), and lower pre-fracture mobility (aOR=0.24). Implant type did not significantly influence either outcome. Conclusions: Early fixation failure is primarily influenced by fracture instability, osteoporosis severity, and fixation quality, whereas early mortality reflects comorbidity burden and frailty. Incorporating comorbidity burden, bone quality, and pre-fracture mobility into preoperative assessment may improve risk stratification and guide personalized perioperative management in elderly patients with intertrochanteric femur fractures.